Rationale, design and baseline characteristics of a randomized controlled trial of a cardiovascular quality improvement strategy in India: the C-QIP trial - Singh, Kavita; Nikhare, Kalyani; Gandral, Mareesha; Aithal, Kiran; Patil, Satish G.; Mp, Girish; Gupta, Mohit; Madan, Kushal; Sawhney, J. P. S.; Ali, Kamar; Kondal, Dimple; Jindal, Devraj; et al. (American heart journal, 2024)
Background - Quality of chronic care for cardiovascular disease (CVD) remains suboptimal worldwide. The Collaborative Quality ImProvement (C-QIP) trial aims to develop and test the feasibility and clinical effect of a multicomponent strategy among patients with prevalent CVD in India. - Methods - The C-QIP is a clinic-based, open randomized trial of a multicomponent intervention vs usual care that was locally developed and adapted for use in Indian settings through rigorous formative research guided by Consolidated Framework for Implementation Research (CFIR). The C-QIP intervention consisted of 5 components: 1) electronic health records and decision support system for clinicians, 2) trained nonphysician health workers (NPHW), 3) text-message based lifestyle reminders, 4) patient education materials, 5) quarterly audit and feedback reports. Patients with CVD (ischemic heart disease, ischemic stroke, or heart failure) attending outpatient CVD clinics were recruited from September 2022 to September 2023 and were randomized to the intervention or usual care arm for at least 12 months follow-up. The co-primary outcomes are implementation feasibility, fidelity (ie, dose delivered and dose received), acceptability, adoption and appropriateness, measured at multiple levels: patient, provider and clinic site-level, The secondary outcomes include prescription of guideline directed medical therapy (GDMT) (provider-level), and adherence to prescribed therapy, change in mean blood pressure (BP) and LDL-cholesterol between the intervention and control groups (patient-level). In addition, a trial-based process and economic evaluations will be performed using standard guidelines. - Results - We recruited 410 socio-demographically diverse patients with CVD from 4 hospitals in India. Mean (SD) age was 57.5 (11.7) years, and 73.0% were males. Self-reported history of hypertension (48.5%) and diabetes (41.5%) was common. At baseline, mean (SD) BP was 127.9 (18.2) /76.2 (11.6) mm Hg, mean (SD) LDLc: 80.3 (37.3) mg/dl and mean (SD) HbA1c: 6.8% (1.6%). At baseline, the GDMT varied from 62.4% for patients with ischemic heart disease, 48.6% for ischemic stroke and 36.1% for heart failure. - Conclusion - This study will establish the feasibility of delivering contextually relevant, and evidence-based C-QIP strategy and assess whether it is acceptable to the target populations. The study results will inform a larger scale confirmatory trial of a comprehensive CVD care model in low-resource settings. - Trial registration - Clinical Trials Registry India: CTRI/2022/04/041847; Clinicaltrials.gov number: NCT05196659.
Online verfügbar: 20. Juli 2024, Artikelversion: 16. August 2024
Gesehen am 07.11.2024